Reduced Ovarian Glyoxalase-I Activity by Dietary Glycotoxins and Androgen Excess: A Causative Link to Polycystic Ovarian Syndrome - Kandaraki, Eleni (ScholarOne, 2012)
Glyoxalase detoxification system composed of glyoxalase (GLO)-I and GLO-II is ubiquitously expressed and implicated in the protection against cellular damage because of cytotoxic metabolites such as advanced glycation end products (AGEs). Recently, ovarian tissue has emerged as a new target of excessive AGE deposition and has been associated with either a high AGE diet in experimental animals or hyperandrogenic disorders such as polycystic ovarian syndrome (PCOS) in humans. This study was designed to investigate the impact of dietary AGEs and androgens in rat ovarian GLO-I activity of normal nonandrogenized (NAN, group A, n = 18) and androgenized prepubertal (AN) rats (group B, n = 29). Both groups were further randomly assigned, either to a high-AGE (HA) or low-AGE (LA) diet for 3 months. The activity of ovarian GLO-I was significantly reduced in normal NAN animals fed an HA diet compared with an LA diet (p = 0.006). Furthermore, GLO-I activity was markedly reduced in AN animals compared with NAN (p ≤ 0.001) when fed with the corresponding diet type. In addition, ovarian GLO-I activity was positively correlated with the body weight gain (r(s) = 0.533, p < 0.001), estradiol (r(s) = 0.326, p = 0.033) and progesterone levels (r(s) = 0.500, p < 0.001). A negative correlation was observed between GLO-I activity and AGE expression in the ovarian granulosa cell layer of all groups with marginal statistical significance (r(s) = −0.263, p = 0.07). The present data demonstrate that ovarian GLO-I activity may be regulated by dietary composition and androgen levels. Modification of ovarian GLO-I activity, observed for the first time in this androgenized prepubertal rat model, may present a contributing factor to the reproductive dysfunction characterizing PCOS.